The importance of measuring customer satisfaction in palliative care. (March 2016) - Turriziani, Adriana; Attanasio, Gennaro; Scarcella, Francesco; Sangalli, Luisa; Scopa, Anna; Genualdo, Alessandra; Quici, Stefano; Nazzicone, Giulia; Ricciotti, Maria Adelaide; La Commare, Francesco
In the last decades, palliative care has been more and more focused on the evaluation of patients' and families' satisfaction with care. However, the evaluation of customer satisfaction in palliative care presents a number of issues such as the presence of both patients and their families, the frail condition of the patients and the complexity of their needs, and the lack of standard quality indicators and appropriate measurement tools. In this manuscript, we critically review existing evidence and literature on the evaluation of satisfaction in the palliative care context. Moreover, we provide – as a practical example – the preliminary results of our experience in this setting with the development of a dedicated tool for the measurement of satisfaction.